A Case Report of Phenobarbital for Proportionate Sedation to Control Refractory Symptoms at the End of Life in an Opioid Tolerant Patient. (3rd July 2021) - Jones, Jessica F.; Hirst, Jeremy M.; Edmonds, Kyle P.; Atayee, Rabia S.
Abstract: End of life (EoL) and refractory symptom management is a growing clinical topic and there is minimal literature to support effective treatment strategies, especially in individuals with a substance use disorder or opioids and/or benzodiazepine tolerance. We report the successful use of phenobarbital for proportionate EoL sedation in a 57-year-old man with opioid use disorder (heroin) and metastatic urothelial carcinoma presenting to an acute care hospital with intractable back pain related to bone metastases. During his hospitalization, his daily opioid requirement exceeded 1 gram of morphine equivalent daily dose (MEDD) with suboptimal pain control. The patient's clinical course was complicated by active heroin withdrawal, psychosocial suffering, and disease progression. Despite use of high-dose opioids and benzodiazepines, pain and anxiety were poorly controlled. After an acute medical decompensation, a goals of care discussion was held with his family and a determination with informed consent was made to change patient status to do not attempt resuscitation and proportionate sedation with phenobarbital was initiated to target refractory pain and agitation. Phenobarbital was continued for approximately 15 hours before patient peacefully died. Findings from this case report demonstrate the successful use of phenobarbital in opioid use disorder and benzodiazepine tolerance with intractable pain.